Management of anthracnose disease of cotton (Gossypium spp.) incited by Colletotrichum gossypii using fungicides - YADAV, LOKESH; YADAV, NARESH KUMAR; MALIK, VINOD KUMAR; VASHISHT, PREETI; AAKASH; YADAV, PANKAJ (The Indian Journal of Agricultural Sciences, 2025)
Anthracnose, caused by Colletotrichum gossypii, poses a significant increasing hazard to cotton (Gossypium spp.) crops. The present study was carried out during rainy (Kharif) seasons of 2020 and 2021 at Cotton Research Station, Sirsa, Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana aimed to assess the efficiency of novel fungicides over in vitro as well as in vivo condition against C. gossypii, the causative agent of anthracnose disease in cotton. This experiment was carried on Bt (RCH 773) and non Bt (H1098i) cotton susceptible cultivars in randomized block design (RBD) with four replications for each treatment.. The highest growth inhibition was observed when using the fungicide Azoxystrobin 18.2% + Difenoconazole 11.4% sc (90.48%), followed by Metiram 55% + Pyraclostrobin 5% wg (84.57%). Minimum disease intensity was observed with the fungicide Azoxystrobin 18.2% + Difenoconazole 11.4% sc in cotton cultivars i.e. Bt (7.01%) and non Bt (8.20%) during the years of evaluation with the maximum seed cotton yield of 2590 kg/ha as well as 2105 kg/ha, respectively. The results of this experiment reported that all the fungicides tested have great potential in managing anthracnose disease of cotton and recorded fruitful results as compared to untreated check.